Zen and the art of motorcycle maintenance : an inquiry into values - Pirsig, Robert M. (New York : Morrow, 1999)
A father and his eleven-year-old son take a motorcycle trip across the country, and together, the two learn about life, love, and identity.
Wilson's Senior High School, November 2002
Wilson's Public Library
New York Times
Young Adult
Keywords: Pirsig, Robert M; Values